Expert opinions on the first-line pharmacological treatment for delirium in Japan: a conjoint analysis. (18th January 2016) - Okumura, Yasuyuki; Hatta, Kotaro; Wada, Ken; Takeuchi, Takashi; Kishi, Yasuhiro; ,
ABSTRACT: Background: There is little expert consensus as to which drugs should comprise the first-line pharmacological treatment for delirium. We sought to assess experts' opinions on the first-line oral and injection drugs for delirium associated with a diverse range of clinical features using a rating-based conjoint analysis. Methods: We conducted a cross-sectional study. We mailed a questionnaire to all consultation-liaison psychiatrists/educators certified by the Japanese Society of General Hospital Psychiatry. Results: Of 136 experts (response rate: 27.5%), more than 68% recommended the use of risperidone or quetiapine administered orally for hyperactive delirium, except in patients with comorbid diabetes and renal dysfunction. More than 67% recommended the use of haloperidol administered intravenously for hyperactive delirium if an intravenous line has been placed. No oral or injection drugs were recommended by over half of experts for treatment of hypoactive delirium with any clinical features. Conclusions: In the absence of a definitive treatment trial, there are both areas of agreement and a lack of consensus regarding the first-line drug. Efforts are needed to routinely collect information that would allow a comparison of the effectiveness and safety of various drugs in real-world clinical practice.